2020
DOI: 10.1021/acs.analchem.0c00293
|View full text |Cite
|
Sign up to set email alerts
|

Middle Level IM–MS and CIU Experiments for Improved Therapeutic Immunoglobulin Subclass Fingerprinting

Abstract: Most of the current FDA and EMA approved therapeutic monoclonal antibodies (mAbs) are based on humanized or human IgG1, 2 or 4 subclasses and engineered variants. On the structural side, these subclasses are characterized by specific interchains disulfide bridge connections. Different analytical techniques have been reported to assess intact IgGs subclasses, with recently special interest in native ion mobility (IM) and collision induced unfolding (CIU) mass spectrometry (MS). However, these two techniques exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 44 publications
4
52
0
Order By: Relevance
“…Altogether, these results suggest that the chemical conjugation process does not drastically affect the overall global conformation of the mAb. However, drawing clear-cut conclusions solely from nIM-MS measurement for mAbs with very close conformations remains challenging at both intact and middle-up levels due to the low resolution of linear TWIMS [ 50 ]. The preliminary CCS measurements are the rationale for performing further CIU experiments, as an alternative to tackle small conformational variations that would result in differences in CIU patterns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these results suggest that the chemical conjugation process does not drastically affect the overall global conformation of the mAb. However, drawing clear-cut conclusions solely from nIM-MS measurement for mAbs with very close conformations remains challenging at both intact and middle-up levels due to the low resolution of linear TWIMS [ 50 ]. The preliminary CCS measurements are the rationale for performing further CIU experiments, as an alternative to tackle small conformational variations that would result in differences in CIU patterns.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate that CIU approaches offer clear benefits over standard nIM-MS experiments to detect subtle conformational differences that translate into different CIU patterns. In addition, CIU data have been reported to correlate with unfolding patterns observed using differential scanning calorimetry (DSC), suggesting a solution-phase memory effect of mAbs products in the gas phase [ 33 , 50 ]. CIU offers significant benefits over DSC, with improved sensitivity and selectivity, and thus, appears as an appealing approach to acquire conjugation-dependent gas-phase stability shift information for biotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, SEC-CIU fingerprints provide the same level of information as nanoESI-or ESI-CIU. Previous works have demonstrated that mAbs subclasses, which namely differ in their number and bridging of disulfide bonds, could be classified based on their unfolding patterns 7,28 . To benchmark our SEC-CIU strategy, we further applied it to the analysis of three mAbs belonging to different subclasses, adalimumab (IgG1), panitumumab (IgG2) and reslizumab (IgG4).…”
Section: Proof Of Concept Of Sec-ciu For Igg1 Analysismentioning
confidence: 99%
“…In particular, Tian et al 7 demonstrated that subtle differences between intact mAbs subclasses, with different numbers and patterns of disulfide bridges, could be distinguished based on their gas-phase unfolding. Recently, Botzanowski et al expanded this strategy to the middle-level classification of mAbs subclasses, which provides a more clear-cut categorization than the intact level 28 .…”
Section: Introductionmentioning
confidence: 99%
“…This technique appeared to be highly valuable for therapeutic mAb products. 18 , 19 , 27 30 In an attempt to automate CIU workflows, Deslignière et al have proposed a SEC–CIU setup that allows recording CIU fingerprints in a rapid manner. 31 …”
Section: Introductionmentioning
confidence: 99%